Can a nightside geomagnetic Delta H observed at the equator manifest a penetration electric field?. Issue 6 (6th June 2013) - Wei, Y.; Fraenz, M.; Dubinin, E.; He, M.; Ren, Z.; Zhao, B.; Liu, J.; Wan, W.; Yumoto, K.; Watari, S.; Alex, S.
Abstract : [1] A prompt penetration electric field (PPEF) usually manifests itself in the form of an equatorial ionospheric electric field being in correlation with a solar wind electric field. Due to the strong Cowling conductivity, a PPEF on the dayside can be inferred from Delta H (ΔH), which is the difference in the magnitudes of the horizontal (H) component between a magnetometer at the magnetic equator and one off the equator. This paper aims to investigate the performance of ΔH in response to a PPEF on the nightside, where the Cowling conductivity is not significant. We first examine the strongest geomagnetically active time during the 20 November 2003 superstorm when the Dst drops to −473 nT and show that the nightside ΔH can indeed manifest a PPEF but with local time dependence and longitude dependence. We then examine a moderately active time by taking advantage of the multiple‐penetration event during 11–16 November 2003 when the Dst remains greater than −60 nT. During this event, a series of PPEF pulses recorded in Peru, Japan, and India form a database, allowing us to examine PPEF effects at different local times and longitudes. The results show that (1) the nightside ΔH was caused by attenuation of the effects of the polar electric field with decreasing latitude; (2) the nightside ΔH can manifest a PPEF at least in the midnight‐dawn sector (0000–0500 LT), but not always; and (3) the magnitude of the nightside ΔH in the midnight‐dawn sector in Peru is on average only 1/18 of that of the dayside ΔH in response to a given PPEF. Key Points: The nightside delta‐H sometimes can manifest PPEF in midnight‐dawn sector The nightside delta‐H is an attenuated effect of polar electric field The performance of delta‐H as an indicator of PPEF exhibits longitude bias